ANALYSIS OF FEATURES OF ELECTRONIC MANNEQUINS AND BODY SCANNERS FOR CLOTHING DESIGN AND VISUALIZATION - Protsyk, Bohdan; Gerasymenko, Olena; Pashkevych, Kalyna; Liuklian, Nadiia; Kass, Bohdan (Theory and practice of design, 2024)
Purpose. To analyze the peculiarities of the use of electronic mannequins and body scanners in the processes of design and visualization of clothes; provide a description of their functional and technical capabilities on the example of software products of leading global companies; to determine the relationship between electronic mannequins and body scanners in the context of their influence on the quality and efficiency of clothing creation processes. Methodology of research is determined by a comprehensive study of the subject and includes: methods of analysis, synthesis, induction, method of structural and systematic analysis of sources. Results. An analysis of literary sources on the subject of three-dimensional visualization and clothing design was carried out. Features of today’s electronic mannequins and body scanners are provided, and how these technologies interact and complement each other in creating high-quality designs and visualization of clothing. It was determined that 3D scanners allow scanning of the anatomical characteristics of the human body in order to create a virtual electronic mannequin. This process uses relevant rendering software such as Clo3D, Optitex – 3D Runway Design, Assyst – 3D Vidya and BROWZWEAR – VStitcher. These aspects testify to the perspective and importance of the introduction of modern technologies in the field of clothing design and production. Scientific novelty. Based on the analysis, a description of the functional and technical aspects of electronic mannequins and body scanners was formed, which allows us to determine their specifics in the context of clothing production and design. Practical relevance. The results of the research provide practical value, serving as a basis for improving modern technologies in the field of clothing design, as well as determining the prospects for their use in the fashion industry.